Problems and pitfalls in grading of bone marrow fibrosis, collagen deposition and osteosclerosis – a consensus‐based study. Issue 6 (20th November 2015) - Kvasnicka, Hans Michael; Beham‐Schmid, Christine; Bob, Roshanak; Dirnhofer, Stephan; Hussein, Kais; Kreipe, Hans; Kremer, Marcus; Schmitt‐Graeff, Annette; Schwarz, Stephan; Thiele, Juergen; Werner, Martin; Stein, Harald
Abstract : Aims: In the era of potentially disease‐modifying agents such as Janus kinase inhibitors, accurate grading and differentiation of bone marrow (BM) fibrosis has become more relevant to assess staging of disease and therapeutic effects. However, different fibrosis grading models have been used in the past without uniformity, including the proposal by the World Health Organization. Current scoring systems are based only on reticulin fibrosis. Therefore, additional assessment of collagen and the grade of osteosclerosis appear to be essential to discriminate all components of the complex BM fibrous matrix. Methods and results: We evaluated problems and pitfalls regarding staining techniques and the interpretation of reticulin fibrosis on a total of 352 samples. Furthermore, we propose a minor modification of the current grading and separate scoring for collagen deposition and osteosclerosis. Reproducibility of gradings was tested among 11 haematopathologists in a blinded assessment. Overall, the inter‐rater reliability of all three grading systems ranged between 0.898 and 0.926. Conclusions: A standardized assessment of BM fibrosis with differentiation between reticulin, collagen and osteosclerosis is recommended to evaluate the various components of the fibrous matrix which may be delinked after therapy. In this regard, quality of staining and application of laboratory standards enable a highly reproducible scoring.